Off-axis microsphere photolithography patterned nanohole array and other structures on an optical fiber tip for glucose sensing. Issue 42 (28th July 2021) - Liu, Jiayu; Jasim, Ibrahem; Liu, Tao; Huang, Jie; Kinzel, Edward; Almasri, Mahmoud
Abstract : Off-axis microsphere photolithography (MPL) was used as a method to create a plasmonic fiber-based sensor for glucose sensing. Sensitivity of 906 nm per RIU has been achieved. And multiple nanostructures have been successfully created on a fiber tip. Abstract : Microsphere photolithography (MPL) using off-axis UV exposure is a technique that uses a layer of self-assembled microspheres as an optical mask to project different periodic nanopatterns. This paper introduces MPL as an alternative fabrication technique to pattern complex metasurfaces on an optical single mode fiber tip as a sensor for measuring refractive index. Based on the hexagonal close packing microsphere array, complicated metasurfaces were successfully created by changing the UV illumination angle. Using the same self-assembled microspheres monolayer, multiple UV illumination jets were projected to create multiple hole group patterns. Fiber sensors with three-hole group and four-hole group patterns were fabricated and tested with different glucose concentrations in water. The different concentration solutions have various refractive indexes, which result in the shift of the metasurface resonant wavelength, represented as sensitivity. The testing results show that the three-hole group and four-hole group have the sensitivity of 906 nm per RIU and 675 nm per RIU, respectively. Finite element analysis was used to model the fiber sensor's surrounding with different refractive index solutions. These new pattern metasurface coated fibers' refractive index sensitivity has increased by 40% compared to our previous work, while the technique still provides a cost-effective, flexible, high-throughput fabrication of the fiber sensor.